2019
DOI: 10.1016/j.heliyon.2019.e01753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dye and temperature on the physico-mechanical properties of jute/PP and jute/LLDPE based composites

Abstract: Jute fabrics and unidirectional jute fiber reinforced polypropylene (PP) and linear low density polyethylene (LLDPE) based composites were prepared successfully by compression molding technique. The unidirectional jute fiber was treated with Reactive Orange HB® and Deep Blue LW® dye to investigate physico-mechanical properties. The Reactive Orange HB® treated composites showed relatively better mechanical properties than the Deep Blue LW® treated composites. The jute fiber-based composites showed higher mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…It also shows that up to 20% the strength is higher than that of pure PP. Similar effect was found by Rashed and Rizvi [5], Shabname Ele [6], Bipasha Bose [3]. apparent that elongation decreases very slightly with the increasing fiber content.…”
Section: Flexural Strengthsupporting
confidence: 85%
See 1 more Smart Citation
“…It also shows that up to 20% the strength is higher than that of pure PP. Similar effect was found by Rashed and Rizvi [5], Shabname Ele [6], Bipasha Bose [3]. apparent that elongation decreases very slightly with the increasing fiber content.…”
Section: Flexural Strengthsupporting
confidence: 85%
“…The use of natural fibers, derived from annually renewable source, as reinforcing fibers in both thermoplastic and thermosetting matrix composites provides positive benefits with respect to ultimate disposability and raw material utilization [1][2][3][4][5][6]. Coir fiber has received considerable attention for its diversified use both in academic and industrial research.…”
Section: Introductionmentioning
confidence: 99%
“…This change in material behavior was also seen in Figure 11, where the extensions at peak forces gradually decreased from HDPE-Jute to PP-Jute to Nylon-Jute composites. as reported by other researchers in the literature [34]. The mechanical properties of jute fiber were much higher than the matrices [4].…”
Section: Characteristics Of Jute Fabric and Compositessupporting
confidence: 81%
“…Rahaman et al [34] reported production of jute fabric reinforced composites with polypropylene (PP) and linear low-density polyethylene (LLDPE) reinforced with jute fabrics by compression molding technique. Better mechanical properties were observed in the polypropylene-based composites compared to that of LLDPE-based composite.…”
Section: Introductionmentioning
confidence: 99%
“…The hazardous effects of handling the radiation source are relatively less in case of UV radiation than the gamma radiation. These are the main reasons for selecting UV radiation sources for the betterment of mechanical properties of prepared materials [7][8][9][10][11]. Monomer treatment is one of the best methods for the improvement of the properties of the composite materials [12][13][14].…”
Section: Introductionmentioning
confidence: 99%